On limits for wind power generation. (2nd December 2004) - Soder, Lennart
The amount of wind power in the world increases fast. The background for this development is improved technology, decreased costs for the units and an increased concern of the environmental problems of competing technologies such as fossil fuels. For the future, it is now interesting to evaluate where the limits are for wind power generation, and which points are crucial. Since there is no power from the wind when there is no breeze, the customers have to get power from other sources during these situations. The question then is whether it is the power system that sets the limits or it is the environmental consequences or the economy? In this paper, these questions will be discussed with focus on power system integration. The results from several case studies are also presented.